PENGARUH METODE PEMBELAJARAN BRAINSTORMING TERHADAP KETERAMPILAN BERPIKIR KREATIF PADA MATERI VIRUS KELAS X DI SMA NEGERI 1 PLAKAT TINGGI - Jhon Riswanda; Sulton Nawawi; Dadang Setiawan (Bioilmi: Jurnal Pendidikan, 2019)
This study aims to determine the effect of Brainstorming learning method influence on creative thinking skills on Class X Virus material in SMA N 1 Plakat Tinggi MUBA Regency. This research uses the design of Nonequivalent Control Group Design research with Quasi Experiment method. The sample of this research is 78 students. Based on the results of data analysis students' creative thinking skills show that the implementation of learning using Brainstorming learning method is better than conventional methods. This can be seen from the calculation of t-test sig titung 0.000 < 0.005, then Ha accepted and Ho rejected. The result of analysis of the average increase of mastery of experimental creative thinking skill is 87.4% while the students 'thinking skill in the control class is 77.4% meaning that the students' creative thinking skill is higher than the creative thinking skill of the control class. So, it can be concluded that the method of Brainstorming influence the creative thinking skills of students class X MIPA SMA N1 Plakat Tinggi MUBA regency.